Networking Essentials, Third Edition - Beasley, Jeffrey; Nilkaew, Piyasat (Pearson IT Certification, 2012)
Thoroughly updated to reflect CompTIA's Network+ N10-005 exam, Networking Essentials, Third Edition, is a practical, up-to-date, and hands-on guide to the basics of networking. Written from the viewpoint of a working network administrator, it requires absolutely no experience with either network concepts or day-to-day network management. Networking Essentials, Third Edition, includes expanded coverage of cabling, a new introduction to IPv6, and new chapters on basic switch configuration and troubleshooting. Its wireless and security chapters now focus strictly on introductory material, and you will also find up-to-date introductions to twisted-pair and fiber optic cabling, TCP/IP protocols, Internet and LAN interconnections, and basic network problem identification and resolution. Clear goals are outlined for each chapter, and every concept is introduced in easy to understand language that explains how and why networking technologies are used. Each chapter is packed with real-world examples and practical exercises that reinforce all concepts and guide you through using them to configure, analyze, and fix networks. Key Pedagogical Features NET-CHALLENGE SIMULATION SOFTWARE provides hands-on experience with entering router and switch commands, setting up functions, and configuring interfaces and protocols WIRESHARK NETWORK PROTOCOL ANALYZER presents techniques and examples of data traffic analysis throughout PROVEN TOOLS FOR MORE EFFECTIVE LEARNING & NETWORK+ PREP, including chapter outlines, summaries, and Network+ objectives WORKING EXAMPLES IN EVERY CHAPTER to reinforce key concepts and promote mastery KEY TERM DEFINITIONS, LISTINGS & EXTENSIVE GLOSSARY to help you master the language of networking QUESTIONS, PROBLEMS, AND CRITICAL THINKING QUESTIONS to help you deepen your understanding.